Problem-based obstetric ultrasound - Thilaganathan, Basky; Sairam, Shanti; Papageorhiou, Aris T.; Bhide, Amar (Informa Healthcare USA, Inc., 2009)
This book contains a series of clinical cases that address and illustrate difficult problems in obstetric ultrasound. The approach is strongly didactic and will aid trainees in maternal-fetal medicine and obstetrics to appreciate potential pitfalls and recognize rare presentations. Each case sets oout one page of text, then one of treatment algorithms, and then presents sample ultrasound scans. Learning objectives are given for each case, together with a short list of references and background reading